Tinjauan Hukum Tindak Pidana Pencurian Hewan Ternak di Desa Palakahembi (Studi Kasus Kecamatan Pandawai Sumba Timur) - Awa, Rambu Ana; Maramba, Rambu Susanti Mila; Indah, Rambu Hada (Media Hukum Indonesia (MHI), 2024)
The state has an obligation to create a peaceful and prosperous society. However, in realizing this, there are still many obstacles/problems in society, namely the existence of crime. Crime is a social problem that always occurs within society. One type of crime is livestock theft. One of the locations where the crime of animal theft occurred is in Palakehembi Village, East Sumba Regency. Therefore, this research will examine the legal review of livestock theft. The object of this research is theft, so the method used is normative-empirical and employs a statute approach and a case approach.